The collected works - Arnáiz Barón, Rafael (Monastic wisdom series, 2022)
"When he was twenty-one years old, Saint Rafael Arnáiz left behind the comforts of his wealthy family and an unfinished degree in architecture to join the Trappist-Cistercian abbey of San Isidro de Dueñas. A sudden onset of diabetes and the beginning of the Spanish Civil War (1936-1939) turned his monastic journey into an unusual one. Rafael developed a solid spirituality, which in its simplicity is a straight path to holiness. He has been compared to mystics like Teresa of Avila and John of the Cross, whose writings inspired him, and his theology of the cross, born from his prayer, places him in continuity with the best of the monastic tradition. In his letters and journals, compiled in this volume, he speaks of the joys and struggles of striving to live for God alone"--